1987
DOI: 10.1364/ol.12.000891
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of the Xe iii 109-nm laser using traveling-wave laser-produced-plasma excitation

Abstract: We describe the construction and operation of a 109-nm, photoionization-pumped, single-pass laser in Xe III. The laser is pumped by soft x rays emitted from a laser-produced plasma in a traveling-wave geometry. Using a 3.5-J, 300-psec, 1064-nm laser pump pulse, we measure a small-signal gain coefficient of 4.4 cm(-1) and a total small-signal gain of exp(40). The laser is fully saturated and produces an output energy of 20 microJ in a beam with 10-mrad divergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…This, together with the short amount of time available for population inversion requires using ultrashort pump pulses with a traveling-wave pumping geometry, which provides exact synchronization between the pump pulse and the generated x-ray pulse. Sher et al (Sher et al, 1987) have used grazing incidence excitation for nearly synchronous traveling-wave pumping of an XUV laser at 109 nm wavelength in Xe (Fig. 5).…”
Section: Traveling-wave Excitation Of X-ray Lasersmentioning
confidence: 99%
“…This, together with the short amount of time available for population inversion requires using ultrashort pump pulses with a traveling-wave pumping geometry, which provides exact synchronization between the pump pulse and the generated x-ray pulse. Sher et al (Sher et al, 1987) have used grazing incidence excitation for nearly synchronous traveling-wave pumping of an XUV laser at 109 nm wavelength in Xe (Fig. 5).…”
Section: Traveling-wave Excitation Of X-ray Lasersmentioning
confidence: 99%
“…Gains of about exp (7) were first observed in the Xe+ 2 Auger system using a 55 J 1064 nm pump laser [5]. Subsequent optimization of operating parameters [7], and the development of new pumping geometries [8] resulted in an equivalent small signal gain of exp(33), and a saturated ouput energy of one microjoule using a 0.5 J pump laser [9]. Our present system achieves gains of about exp ( 2 5) and output energies of 1 J using a 250 mJ, -100 psec pump pulse, the lowest pump energy reported for saturated output to date.…”
Section: G-044mentioning
confidence: 99%
“…Experiments by Yin et al 3 showed that comparable gains on this transition could be obtained with less than 1 J of pumping energy. Recently Sher et al 4 used a traveling-wave geometry to obtain a small-signal gain of exp (40) and a saturated output energy of 20 LJ at 109 nm.In this Letter we follow the proposal of Mendelsohn and Harris 5 to obtain gain by selective super CosterKronig decay of photoionization-pumped Zn I. A super Coster-Kronig decay process is a subclass of an Auger process in which the initial hole, the jumping electron, and the departing electron all occupy the same n shell.…”
mentioning
confidence: 99%
“…Experiments by Yin et al 3 showed that comparable gains on this transition could be obtained with less than 1 J of pumping energy. Recently Sher et al 4 used a traveling-wave geometry to obtain a small-signal gain of exp (40) and a saturated output energy of 20 LJ at 109 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation